Thoracoscopic esophagectomy with left recurrent laryngeal nerve monitoring for thoracic esophageal cancer in a patient with a right aortic arch: a case report - Ninomiya, Yamato (Surg Case Rep, 2020)
BACKGROUND: Surgery for cases of thoracic esophageal cancer with a right aortic arch is rare, and the anatomic abnormalities in such patients necessitate a different surgical approach. Since the position of the recurrent laryngeal nerve often differs from the usual in these cases, the lymph node dissection around the recurrent laryngeal nerve, which is an important step in surgery for thoracic esophageal cancer, requires careful attention. There are some reports on the usefulness of intraoperative recurrent laryngeal nerve monitoring during esophageal cancer surgery. Herein, we report a case of successful thoracoscopic esophagectomy for esophageal cancer in a patient with a right aortic arch using intraoperative recurrent laryngeal nerve monitoring. CASE PRESENTATION: A 70-year-old man was diagnosed as having esophageal cancer (Ut, type 0-IIc, T1b/MtLt, type 0-IIc, T1b, N2, M0, cStage II) and was treated by neoadjuvant chemoradiotherapy followed by radical surgery. Preoperative CT examination revealed a right aortic arch, and based on the findings of 3D-CT, we classified the right aortic arch as type IIIB1 (Edwards classification), which is the most frequent type of right aortic arch. We performed thoracoscopic esophagectomy via a left thoracic approach with the patient placed in the prone position, cervical esophagogastric conduit reconstruction via the retrosternal route, and three-field lymph node dissection. Although Kommerell’s diverticulum could be easily confirmed, the descending aorta took a meandering course, making it difficult for the esophagus to be mobilized and detached and therefore also to identify the ductus arteriosus and left recurrent laryngeal nerve. Intraoperative recurrent laryngeal nerve monitoring using NIM-RESPONSE® 3.0 (Medtronic Japan, Tokyo, Japan) allowed the position of the left recurrent laryngeal nerve to be accurately determined, and upper mediastinal lymph node dissection and mobilization of the upper thoracic esophagus were performed safely. Postoperatively, the patient showed no evidence of recurrent laryngeal nerve palsy, but needed conservative treatment for anastomotic leakage. The patient was discharged 46 days after the surgery. CONCLUSION: It was suggested that intraoperative recurrent laryngeal nerve monitoring is useful in esophageal cancer with a right aortic arch undergoing surgery, in whom anatomic abnormalities of the recurrent laryngeal nerve can be expected.